COUNTER PRESSURE UNTUK MENGURANGI RASA NYERI PERSALINAN (EVIDENCE BASED CASE REPORT): Indonesia (Jurnal Kesehatan Siliwangi, 2022)
Due to the uterus' natural activity, almost all pregnant women who undergo labor feel discomfort. As lessen discomfort, pain management is required. The control pressure technique is one of the non-drug ways to lessen discomfort. This case study uses data to support its conclusion that the counter pressure technique is beneficial in lowering labor discomfort. This evidence-based case report strategy uses journal database searches. Using the search terms "Sacral massage OR Long Back massage OR Counter pressure massage AND labor AND birthING AND Pain Management" on December 18, 2022, a total of 1,833 articles were obtained. A selection was reached through inclusion according to clinical questions using full text, which is only available for the previous 5 years. The VIA method was used to assess, and 4 journal articles were discovered to meet the criteria. According to a review of journals on counter pressure, this strategy can reduce discomfort brought on by the uterus' physiological activity throughout the mother's experience. This method uses massage to reduce pain and produce a psychologically soothing experience as a non-pharmacological alternative. Conclusion: Counter pressure can be utilized as a pain management approach to lessen labor pain